2001
DOI: 10.1149/1.1341246
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Characterization of Tungsten Chemical and Mechanical Polishing Processes

Abstract: Due to the complexity of chemical mechanical polishing ͑CMP͒ in general and metal CMP in particular, modeling of CMP processes has been pursued only minimally in the literature. A fundamental understanding of these metal CMP processes is needed to minimize manufacturing and development costs that will continue to escalate as more devices migrate to subhalf-micrometer technologies where metallization schemes are more complicated. In this work, we have used two different models to characterize the tungsten CMP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities. [1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities. [1][2][3][4][5] Current semiconductor fabrication technology for logic and memory devices requires CMP to achieve the required multilevel interconnection densities.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that better uniformity is obtained throughout the wafer with the embossed politex pad than with regular politex pad because of the presence of grooves on the embossed pad [16]. For different patterns of grooves, combined patterns consisting of spiral and logarithmic grooves were shown to impact on several key attributes of the dielectric and copper CMP processes in terms of slurry retention, hydrodynamic pressure, tribological mechanism, and material removal rates [17].…”
Section: Pad Groove Effectsmentioning
confidence: 99%
“…Application of abrasive methods in operations for cutting the ingot of semiconductor material by wafers, for grinding and polishing the wafer surface, which provides removal of cut traces (cut strips, scratches, spallings) and thinning the wafers inevitably leads to creation of a structurally destructed surface layer of a definite depth [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%